INTRAVENOUS FLUORESCEIN ADMINISTRATION SAFETY AT CONFOCAL LASER ENDOMICROSCOPY OF GASTROINTESTINAL TRACT IN CHILDREN - A. A. Shavrov (Junior); A. E. Alexandrov; A. A. Shavrov; A. Y. Kharitonova; G. V. Volynets; A. G. Talalaev (Педиатрическая фармакология, 2013)
Confocal laser endomicroscopy (CLE) is a method of optic biopsy, which allows obtaining histologic presentation of mucous tunic in real time and quickly differentiating between unaltered and inflamed, metaplastic and dysplastic tissue structures, thus developing a new and safe method of early diagnostics of diseases. Intravenous administration of 10% sodium fluorescein is necessary in order to obtain high-contrast images of the structure of digestive tract’s mucous tunic, although there have been no direct indications to that in the world pediatric practice. The authors examined 124 children of 3-18 years of age who received intravenous fluorescein of 5 mg/kg. No severe side effects were revealed at intravenous administration. The authors revealed temporary yellowing of skin and bright coloration of urine. In terms of mild side effects, the authors observed insignificant nausea and emesis in 2 children (1.6%). Strict observation of the selection protocol allows not only avoiding severe complications caused by administration of the drug, but also recommending its use at CLE of digestive tract’s mucous tunic in children.